Arabidopsis PSEUDO-RESPONSE REGULATOR7 Is a Signaling Intermediate in Phytochrome-Regulated Seedling Deetiolation and Phasing of the Circadian Clock - Kaczorowski, Karen A. (American Society of Plant Biologists, 2003)
To identify new components in the phytochrome (phy) signaling network in Arabidopsis, we used a sensitized genetic screen for deetiolation-defective seedlings. Two allelic mutants were isolated that exhibited reduced sensitivity to both continuous red and far-red light, suggesting involvement in both phyA and phyB signaling. The molecular lesions responsible for the phenotype were shown to be mutations in the Arabidopsis PSEUDO-RESPONSE REGULATOR7 (PRR7) gene. PRR7 is a member of a small gene family in Arabidopsis previously suggested to be involved in circadian rhythms. A PRR7–β-glucuronidase fusion protein localized to the nucleus, implying a possible function in the regulation of photoresponsive gene expression. Consistent with this suggestion, prr7 seedlings were partially defective in the regulation of the rapidly light-induced genes CIRCADIAN CLOCK ASSOCIATED1 (CCA1) and LATE ELONGATED HYPOCOTYL (LHY), observable as a premature increase in expression level during the second peak of the biphasic induction profile that is elicited upon initial exposure of dark-grown seedlings to light. A similar 3- to 6-h coordinated advance in peak free-running expression of CCA1, LHY, and TIMING-OF-CAB1, which are considered to encode the molecular components of the circadian oscillator in Arabidopsis, was observed in entrained fully green prr7 seedlings compared with wild-type seedlings. Collectively, these data suggest that PRR7 functions as a signaling intermediate in the phytochrome-regulated gene expression responsible for both seedling deetiolation and phasing of the circadian clock in response to light.